Contributions in medical needle technologies—Geometry, mechanics, design, and manufacturing. Issue 1 (2nd January 2016) - Wang, Yancheng; Li, Weisi; Han, Peidong; Giovannini, Marco; Ehmann, Kornel; Shih, Albert J.
Abstract: This article summarizes the contributions in research on tissue cutting with needles. The geometry of the needle's cutting edges was analytically defined and expressions for the inclination and rake angles of hollow and solid needles and trocars have been derived. Based on the semi-empirical method, finite element model and the fracture mechanics approach, force models of needle insertion were developed. The relationship between the needle's tip geometry and insertion force was established and used in several applications. It was shown, for example, that the cutting edge of the lancet needle can be optimally designed to minimize insertion force or bevel length. The cutting mechanics in rotary needle insertion was investigated along with the exploration of improvements of needle biopsy performance by decreasing the needle cutting and friction forces. The deflections of the needle during insertion were measured to develop a strategy for guiding the needle to the right position in brachytherapy and drug delivery. From an overall perspective, fundamental advances and application problems based on the cutting mechanics of soft tissue for needle were highlighted to lay the foundation for developments of biomedical device and improvements of healthcare procedures.